2017
DOI: 10.4025/jphyseduc.v28i1.2837
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation and Manual Asymmetries: The Effect of the Stimulation on the Manual Dexterity

Abstract: RESUMOO objetivo foi avaliar os efeitos da estimulação transcraniana por corrente contínua (ETCC) sobre o córtex motor primário (M1) nas assimetrias de desempenho manual em uma tarefa de destreza manual. A amostra foi composta por 28 voluntários, destros, do sexo masculino e sem comprometimento neurológico. A tarefa (Grooved Pegboard) consistiu em encaixar 25 pinos em 25 receptáculos, o mais rápido possível. A tarefa foi executada no pré-teste com ambas as mãos para definição do nível de assimetria manual. Uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
3
0
2
Order By: Relevance
“…As predicted, the Met/Met group was more asymmetric than the Val/Met group under the more difficult place condition, but the Val/Met group was more asymmetric than the Met/Met group under the less difficult remove condition. Generally speaking, the place condition was associated with more performance asymmetry than the remove condition, as found in previous studies (Albuquerque et al, 2017;Bryden et al, 2007;Salvador et al, 2017), and under both place and remove conditions, righthanded performance was better than left-handed performance.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As predicted, the Met/Met group was more asymmetric than the Val/Met group under the more difficult place condition, but the Val/Met group was more asymmetric than the Met/Met group under the less difficult remove condition. Generally speaking, the place condition was associated with more performance asymmetry than the remove condition, as found in previous studies (Albuquerque et al, 2017;Bryden et al, 2007;Salvador et al, 2017), and under both place and remove conditions, righthanded performance was better than left-handed performance.…”
Section: Discussionsupporting
confidence: 80%
“…The greater asymmetry for participants during the place condition relative to the remove condition was expected, since the increased task difficulty and greater accuracy demands of the place condition have both been linked with greater lateral asymmetries (Bryden et al, 2007;Vasconcelos & Rodrigues, 2008). Prior studies using the Grooved Pegboard Test to investigate manual asymmetries showed a greater RT when placing the pegs (higher ID) than when removing the pegs (lower ID; Bryden & Roy, 2005;Fernandes, Souza, Sales, & Apolina´rio-Souza, 2018;Lelis-Torres et al, 2017;Salvador et al, 2017). This difference observed in right-and left-hand performance among these participants may have been attributable to contralateral hemisphere specialization for voluntary movement organization and control (Elliott & Roy, 1996).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…O Grooved Pegboard Test é composto por uma superfície com 25 orifícios, cada um possuindo uma reentrância posicionada em diferentes direções, e uma superfície côncava onde são colocados os pinos (FIGURA 1). Os pinos também possuem uma reentrância, que deve coincidir espacialmente com a do orifício para que haja encaixe (SALVADOR et al, 2017;FERNANDES et al 2018).…”
Section: Métodosunclassified